2020
DOI: 10.3390/su12239852
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sustainable Practices in Value Creation and Consumers’ Commitment with Companies’ Commercial Format

Abstract: Sustainable economic models are essential for any economic sector of the country. Companies must manage their relationships with the agents involved in their economic activity through a strategy based on dialogue and the constant pursuit of a balance among economic, social and environmental interests. In this regard, there has been an increase in customers’ interest in products or businesses that display a comparatively higher commitment with workers, the environment, or society as a whole. This study aims at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
1
11
0
5
Order By: Relevance
“…The study of CSR as a philosophy of corporate governance involves different approaches that explain how the interaction between organizations and their social context is triggered by the consequences generated on shareholders and stakeholders [31][32][33]. Many interdisciplinary studies have analyzed the relationships between organizations and their stakeholders, the ethical, philanthropic, normative, economic, social, and environmental aspects of corporate actions, the longitudinal dimension in the implementation of different stages of CSR models as well as their measurement and impact on the creation of corporate value and reputation [16,28,[34][35][36][37][38][39].…”
Section: Strategic Management Of Csr: Models Regulations Legislation and Guidelinesmentioning
confidence: 99%
“…The study of CSR as a philosophy of corporate governance involves different approaches that explain how the interaction between organizations and their social context is triggered by the consequences generated on shareholders and stakeholders [31][32][33]. Many interdisciplinary studies have analyzed the relationships between organizations and their stakeholders, the ethical, philanthropic, normative, economic, social, and environmental aspects of corporate actions, the longitudinal dimension in the implementation of different stages of CSR models as well as their measurement and impact on the creation of corporate value and reputation [16,28,[34][35][36][37][38][39].…”
Section: Strategic Management Of Csr: Models Regulations Legislation and Guidelinesmentioning
confidence: 99%
“…Sun et al [59] found that CSR activities can increase consumer loyalty. Other studies investigated the CSR's impact on the consumer, through its commitment and perception of value [60]; the effect of philanthropic corporate social responsibility on the consumer's attitude and consequently on word of mouth and the willingness to pay more [61]; CSR's direct relationship with the desire to pay a price premium [62]; the relationship of CSR in word of mouth [63]; CSR's influence on word of mouth and purchase repetition, with the brand credibility as a mediator [47]; the direct and positive relationship between CSR and Loyalty [64]; the influence of customer perceptions of CSR on brand equity [37,65]. There are also studies on CSR's relationship with purchase intention, perceived quality, brand image, and brand attitude [44,66].…”
Section: Corporate Social Responsibility and Marketingmentioning
confidence: 99%
“…The study of CSR as a philosophy of corporate governance involves different approaches that explain how the interaction between organizations and their social context is triggered by the consequences generated on shareholders and stakeholders [22][23][24]. Many interdisciplinary studies have analyzed the relationships between organizations and their stakeholders, the ethical, philanthropic, normative, economic, social and environmental aspects of corporate actions, the longitudinal dimension in the implementation of the different stages of CSR models as well as their measurement and impact on the creation of corporate value and reputation [16,[25][26][27][28][29][30][31].…”
Section: Strategic Management Of Csr: Models Regulations Legislation and Guidelinesmentioning
confidence: 99%